Treating rheumatoid arthritis in Latin America: current challenges and future treatment strategies. (April 2012) - Cardiel, Mario H
Mario H Cardiel studied Medicine at The Universidad Michoacana de San Nicolás de Hidalgo in Morelia, Michoacán, Mexico. He obtained his medical degree in 1982 and undertook his Internal Medicine and Rheumatology training at the Instituto Nacional de Ciencias Médicas y Biológicas "Salvador Zubirán" in Mexico City (INCMBSZ) from March 1983 to February 1988. Dr Cardiel then completed a Master in Science in Design, Measurement and Evaluation program at McMaster University, in Hamilton, Ontario, Canada with Dr Peter Tugwell as his mentor. After going back to Mexico and working as a staff researcher and clinical rheumatologist at the Department of Immunology and Rheumatology at the INCMBSZ from November 1989 to June 2004, he was professor at the Universidad Nacional Autónoma de Mexico from 1990 to 2004 in postgraduate programs. In August 2004, he then moved to Morelia, where he is currently Head of the Research Unit "Dr Mario Alvizouri Muñoz" at the Hospital General "Dr Miguel Silva". He has been chairman of the Epidemiology Committee at PANLAR and has belonged to the National Research System since 1990 and has reached the highest level since 2009. Dr Cardiel is the founder of important multinational research groups such as GLADEL (Grupo Latinoamericano del Estudio de Lupus), GLADAR (Grupo Latinoamericano del Estudio de Artritis Reumatoide) and GEEEMA (Grupo de Estudio Epidemiológico de las Enfermedades Musculoarticulares). Dr Cardiel has published more than 100 peer-reviewed articles, having been cited almost 3000 times, and he serves as an editor for several peer-reviewed journals in rheumatology.